Implementasi Projek Penguatan Profil Pelajar Pancasila Dalam Pendidikan Agama Islam di SMAN 3 Palangka Raya - Siti Amaliah; Muslimah Muslimah; Muhammad Redha Anshari (Lembaga Dongan Dosen, 2025)
This study aims to describe the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) in Islamic Religious Education at SMAN 3 Palangka Raya under the theme “Say No to Cyber Bullying” and to analyze its impact on students. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The informants included the P5 coordinator, Islamic Religious Education teachers, and students. The findings reveal that the P5 project was implemented through careful planning, collaboration between teachers and students, and the application of project-based learning that is contextualized with Islamic teachings and Pancasila values. The Islamic Education teacher acted as a facilitator to integrate moral education with the issue of cyber bullying. Evaluation was carried out through observation, reflection, and assessment of student projects. The project had a positive impact on raising students’ awareness in using social media wisely, enhancing critical thinking skills, and strengthening noble character. However, several challenges were encountered, particularly limited time and coordination among teachers. These challenges highlight the need for flexible scheduling and stronger teacher support. This research is expected to serve as a reference for developing character education strategies based on P5 that are relevant to the challenges of the digital era.